HUBUNGAN KEKUATAN OTOT LENGAN DAN KOORDINASI MATA-TANGAN TERHADAP KEMAMPUAN PASSING BAWAH BOLAVOLI PADA TIM PUTRA SMA PONDOK PESANTREN AL-FURQON PEKANBARU - Syam Surya Rocky; Slamet Slamet; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : Based on the results of the author's observations on the Team of the Putra Bolavoli High School Al-Furqon Islamic Boarding School in Pekanbaru. found deficiencies when doing lower passes, this was seen when receiving service balls from opponents, players were still overwhelmed in accepting the ball so that the ball was not as desired. This study aims to determine the relationship of arm muscle strength and eye-hand coordination to the Bolavoli Lower Passing Ability at the Al-Furqon Islamic Boarding School High School Team in Pekanbaru. Based on the results of the research that the author has described in the previous chapter, it can be concluded as follows: there is a relationship between arm muscle strength, where rtab at a significant level α (0.05) = (0.602) means rcount (0.63)> rtab (0.602 ) Then there was no relationship between eye-hand coordination, where the rtab at a significant level α (0.05) = (0.602), means that r count = (0.04) <rtab (0.602), and there is a relationship between arm muscle strength and eye-hand coordination with passing ability under male high school athletes in Al-Furqon Islamic boarding school in Pekanbaru, where rtab at a significant level α (0.05) = (0.602) means r count (0.64)> rtab (0.242).Key Words: Arm Muscle Strength, Eye-Hand Coordination. Volle ball Lower Passing Ability